2018
DOI: 10.3390/ma11060892
|View full text |Cite
|
Sign up to set email alerts
|

Residual Fatigue Properties of Asphalt Pavement after Long-Term Field Service

Abstract: Asphalt pavement is widely used for expressways due to its advantages of flexibility, low cost, and easy maintenance. However, pavement failures, including cracking, raveling, and potholes, will appear after long-term service. This research evaluated the residual fatigue properties of asphalt pavement after long-term field service. Fatigue behavior of specimens with different pavement failure types, traffic load, service time, and layers were collected and characterized. Results indicate that after long-term f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 22 publications
0
16
0
5
Order By: Relevance
“…Traditional dense-graded asphalt mixture is a frequently-used asphalt mixture and is applied widely in the asphalt pavement construction in China [28]. The standard Marshall design method was adopted to prepare the asphalt mixture specimens [29].…”
Section: Methodsmentioning
confidence: 99%
“…Traditional dense-graded asphalt mixture is a frequently-used asphalt mixture and is applied widely in the asphalt pavement construction in China [28]. The standard Marshall design method was adopted to prepare the asphalt mixture specimens [29].…”
Section: Methodsmentioning
confidence: 99%
“…Traditional dense-graded asphalt mixture is a well-graded asphalt mixture and is applied extensively in asphalt pavement construction in China [42]. In this study, the median gradation of asphalt mixture (AC-13) was selected, as shown in Figure 1, and the upper and lower limits of AC-13 are also illustrated.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…On the one hand, high temperature is not good for the asphalt pavement itself. For example, high temperature tends to cause the asphalt mixture to soften easily, and with the continuous rolling of vehicles, it may produce viscous flow and even road distress, such as rutting [1,2]. This greatly increases the maintenance cost and reduces the life of asphalt pavement, which is detrimental to the sustainable development of asphalt pavement.…”
Section: Introductionmentioning
confidence: 99%